Balancing Data Access and Data Protection: The Luxembourg Income Study Experience - Marc Cigrang; John Coder (Luxembourg Income Study (LIS), 1990)
The purpose of this paper is to describe the development and current status of the LIS project with emphasis on the systems that manage and monitor access to the database.
Keywords: 330